Flexural properties loss of unidirectional epoxy/fique composites immersed in water and alkaline medium for construction application - Gomez Hoyos, Catalina (2012)
Epoxy fique composites were evaluated for construction applications and compared with conventional wood used in construction. The composites studied were made with fique fibers treated using Na(OH) solution at 18 w/v%, untreated fique fibers were also used. The matrices were epoxy and epoxy with 5 wt.% of chemically modified C30B montmorillonite. Unidirectional composites of 90 mm × 20 mm × 4 mm were elaborated by pultrusion processing technique. The flexural properties loss occurred over 20 days of composites submitted to three types of environments: (i) water, (ii) saturated calcium hydroxide solution and (iii) mortar with w/c ratio of 0.45 and 540 kg/m3 of cement, cured in a saturated solution of lime stone at 50 °C. Results showed that fiber treatment and montmorillonite addition improved the flexural modulus and strength of composites in 40% and 34% respectively. Moreover the flexural properties of composites before and after ageing resulted comparable or even better than conventional wood used in construction.